Communicating with coaches: Envisioning data - Sands, W. (coachesinfo.com, 1999)
Gymnastics and biomechanics is a natural partnership. If sport scientists can begin to deliver their information to coaches via symposia that coaches attend, publications that are both vivid and easy to understand, and information that serves to solve current coaching problems, author believes that sport science can contribute much more to gymnastics than it currently does. Biomechanists have prided themselves on 'bridging the gap' between science and sport, but few have studied the influence of such efforts. It will behoove all sport scientists to become more intimately familiar with coaches and their needs if the scientist is to have an impact beyond scholarly publications. Biomechanists are among the most crucial specialists that can enhance gymnastics performance.